THE EFFECT OF JOB SATISFACTION, COMPENSATION AND WORK STRESS TO EMPLOYEE WORK COMMITMENT PT. PRIMA KARYA NUSA MEDAN - Viona Violita; Thomas Sumarsan Goh; Nur Subiantoro; Syawaluddin (Jurnal Ekonomi, 2022)
This research was conducted on employees who work at PT. Prima Karya Nusa Medan. The purpose of this study was to determine and analyze the effect of job satisfaction, compensation, and job stress on employees' work commitment. The population and sample in this study amounted to 40 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously job satisfaction, compensation, and job stress have a positive and significant effect on the work commitment of employees of PT. Prima Karya Nusa Medan. Partially, job satisfaction does not affect the work commitment of employees of PT. Prima Karya Nusa Medan. Partially, compensation has a positive and significant effect on the work commitment of employees of PT. Prima Karya Nusa Medan. Partially, work stress does not affect the work commitment of employees of PT. Prima Karya Nusa Medan. The magnitude of the coefficient of determination can be seen from the RSquare value of 0.694 which means job satisfaction, compensation, and work stress are able to explain employee work commitment by 69.4% while the remaining 30.6% is influenced by variables not examined such as: motivation, salary, job promotion , etc.